Systematic Literature Review: Pengaruh Kinerja Keuangan, Corporate Social Responsibility, Koneksi Politik, dan Transparansi Laporan Keuangan terhadap Penghindaran Pajak. - Shobrina Nurul Aisyah; Sinta Apriyani; Vita Khera Amelia; Dien Noviany Rahmatika (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the influence of financial performance, Corporate Social Responsibility (CSR), political connections, and financial report transparency on tax avoidance using the Systematic Literature Review (SLR) approach. Tax avoidance practices remain a significant issue in Indonesia because they can reduce potential state revenue and reflect weak corporate governance. This research method analyzes 45 scientific articles indexed by Sinta in the 2020-2025 period. These articles were selected through a screening stage using the keywords